方程[img=540x84]17da6f5f5a5da14.png[/img]的通解为[img=564x110]17da6f5f6d786d3.png[/img]。( )
举一反三
- 已知f(x)为奇函数,f(5)=6,则f(-5)=( ) A: 6 B: -6 C: ±6 D: 以上都不是
- 逻辑函数[img=143x24]1802e4be694bd2e.png[/img]的最小项表达式为( ) A: F=Σm(0、2、5、7) B: [img=124x24]1802e4be71a0d38.png[/img] C: F=Σm(1、3、6) D: F=Σm(0、1、2、6、7)
- 逻辑函数[img=143x24]1802e4bdeb73643.png[/img]的最小项表达式为( ) A: F=Σm(0、2、5、7) B: [img=124x24]1802e4bdf40624b.png[/img] C: F=Σm(1、3、6) D: F=Σm(0、1、2、6、7)
- 逻辑函数[img=143x24]1802e4c2943001e.png[/img]的最小项表达式为( ) A: F=Σm(0、2、5、7) B: [img=124x24]1802e4c29c3837d.png[/img] C: F=Σm(1、3、6) D: F=Σm(0、1、2、6、7)
- 方程[img=540x84]17d600b4802ff5e.png[/img]的通解为[img=564x110]17d600b48d2c5af.png[/img]。( )